ADSCs Combined with Melatonin Promote Peripheral Nerve Regeneration through Autophagy - Ziqiang Zhang; Mengyu Zhang; Zhixiang Zhang; Yingying Sun; Jiajia Wang; Chenhao Chang; Xinyan Zhu; Monan Li; Yumei Liu (International Journal of Endocrinology)
Background. In the early stage of nerve injury, damaged tissue is cleared by autophagy. ADSCs can promote nerve axon regeneration. However, the microenvironment of the injury was changed, and ADSCs are easily apoptotic after transplantation. Mel plays a role in the apoptosis, proliferation, and differentiation of ADSCs. Therefore, we investigated whether Mel combined with ADSCs promoted peripheral nerve regeneration by enhancing early autophagy of injured nerves. Materials and Methods. SD rats were randomly split into the control group, model group, Mel group, ADSCs group, ADSCs + Mel group, and 3-MA group. On day 7, autophagy was observed and gait was detected on days 7, 14, 21, and 28. On the 28th day, the sciatic nerve of rats’ renewal was detected. Results. After 1 w, compare with the model group, the number of autophagosomes and lysosomes and the expressions of protein of LC3-II/LC3-I and Beclin-1 in the ADSCs + Mel group were prominently increased, while the 3-MA group was significantly decreased. After 4 w, the function of the sciatic nerve in ADSCs + Mel was similar to that in the control group. Compared with the model group, the ADSCs + Mel group significantly increased myelin regeneration and the number of motor neurons and reduced gastrocnemius atrophy. Conclusions. It was confirmed that ADSCs combined with Mel could promote sciatic nerve regeneration in rats by changing the early autophagy activity of the injured sciatic nerve.